Migration as adventure: Swedish corporate migrant families' experiences of liminality in Shanghai. Issue 1 (1st March 2019) - Suter, Brigitte
The post-reform era in China has seen a steady increase in foreign migrants to the country. Swedish intra-corporate families are ambivalent about the move to China, as this causes the family dynamic to shift from a dual-career model to that of a single-career model. Although structural conditions are important in the decision to migrate, the more subjective part of the motivation to engage in mobility is the main focus of this article. Many assert that wanting to 'have an adventure' was a decisive aspect of the decision to migrate. By disentangling this ultimately relational concept, the article analyses the construction of difference in the way China is both imagined and experienced. The article contributes by providing insight into the family dynamics and decision-making involved in taking on an international assignment.